Peranan institusi dalam pembangunan keusahawanan wanita: kajian literatur modal insan, daya saing dan keusahawanan digital - Ayob, Nor Azira; Aziz, Mohd Amar; Ayob, Noor Hadzlida; Abd Hamid, Siti Nur Fathanah; Ahmad, Yarina (Faculty of Administrative Science and Policy Studies, 2023)
This analysis focuses on human capital and competitiveness, as well as the role of institutions in improving the performance of female entrepreneurs. Along with the country's development and progress, the aspect of entrepreneurship develops along with the expansion and improvement of technology, and recently, digital entrepreneurship has become a popular topic of discussion, not to mention the country's global health problem of COVID-19. In general, as a result of this literature review, the government has implemented various efforts to develop women entrepreneurs, particularly in terms of improving entrepreneur performance. Women's participation in the field of entrepreneurship, on the other hand, is perceived to be less prominent than that of male entrepreneurs. Ironically, through the role of institutions, the development of human capital and competitiveness, as well as the use of cutting-edge digital technologies, are emphasised for improving the performance of entrepreneurs. Thus, this concept paper emphasizes aspects of human capital, competitiveness, the using of digital technology as a creative force and the role of institutions as intermediaries to support entrepreneurs, to propose steps and action plans to improve performance and develop the talent of female entrepreneurs to become successful entrepreneurs in accordance with the National Entrepreneurship Policy 2030 (DKN2030). The results of this review will be able to contribute and add information to the development of the scope of knowledge, particularly for entrepreneurs, decision makers, and institutions involved in the development of more creative and innovative entrepreneurs. This is because the current economic scenario necessitates entrepreneurs who not only have good knowledge but are also creative in their use of the latest technology. In fact, high competitiveness aspects are required in accordance with DKN2030 and further assist related parties in formulating and implementing appropriate follow-up actions in addition to being able to enact appropriate support policies and programmes to improve the performance of female entrepreneurs.